PENYULUHAN DAN PENDAMPINGAN PERUMUSAN VISI, MISI, DAN NILAI ORGANISASI PADA BANK SAMPAH RUKUN MAKMUR - Imam Riefly Aditomo; Billy Lutfi Mahanani; Muhammad Irfan Alfarisi (Jurnal Pengabdian Masyarakat Sabangka, 2026)
Rukun Makmur Waste Bank, as a newly established social organization, faced challenges in determining its strategic direction due to the absence of clearly defined vision, mission, and organizati onal values. This issue became the basis for conducting a community service program in the form of counseling and assistance in formula ting the organization’s vision, mission, and values. The activity was carried out through three stages: preparation, implementation, and reporting. The preparation stage included organizational needs analysis and the development of mentoring materials. The implement ation stage was conducted through interactive counseling and participatory assistance to explore the organization’s core values using the framework proposed by Collins and Porras. Furthermore, the reporting stage was conducted as a form of documenting the activity outcomes. The results of the program showed that the organization successfully formulated an initial draft consisting of core values, core purpose, long-term vision, and a future description of the organization. results are expected to serve as strategic guide lines for organization’s development and sustainability in the future.